Knowledge of pregnant women about risk factor of cleft lip and palate at Puskesmas Mutiara, Asahan, Indonesia - Rusdy, Hendry; Syaflida, Rahmi; Hanafiah, Olivia Avriyanti; Ratnaningtyas, Jemima (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Cleft is a congenital abnormal space or gap in the upper lip, alveolus, or palate. This congenital abnormality occurs between the 5th and 10th weeks of pregnancy. Clefts are divided into cleft lip, cleft palate, as well as cleft lip and palate. Cleft lip and palate are caused by the interaction of individual genes with certain environmental factors. Mothers’ knowledge about risk factor of cleft lip and palate may promote better health-related behavior in their pregnancy by increasing the understanding about the risk factor. Unfortunately, until now there is still limited data about this. The purpose of this study was to determine the knowledge of pregnant women about risk factor of cleft lip and palate. This was a descriptive study that used the survey method. This study was conducted using a questionnaire distributed to 67 pregnant women (n = 67). The questionnaire consisted of 13 validated questions. The results of this study found that 10.4% of the respondents had good knowledge, 32.8% of the respondents had moderate knowledge and 56.7% of the respondents had poor knowledge. The overall knowledge of the pregnant women about risk factor of cleft lip and palate at Puskesmas Mutiara Asahan fell in the low category.